A finite element methodology to model flexible tracks with arbitrary geometry for railway dynamics applications. (1st October 2021) - N. Costa, J.; Antunes, P.; Magalhães, H.; Pombo, J.; Ambrósio, J.
Highlights: A Timoshenko beam element to represent curved rails in realistic tracks models. A methodology for flexible railway tracks and wheel-rail contact mechanics. The automated construction of finite element models of 3D railway tracks. A co-simulation between multibody dynamics and the finite element formulation. A method that improves contact forces calculation and eliminates spurious vibrations. Abstract: The dynamic analysis of railway vehicles requires an accurate representation of the vehicle, the track geometry and structure, and their interaction. Generally, flexible track models with curved geometries represent the rails with straight beam elements, which results in a piecewise linear representation of the rails. Consequently, the wheel-rail contact mechanics are not properly captured, and the wheel-rail contact forces present spurious high-frequency oscillations. This work proposes a novel approach to model flexible railway tracks with arbitrary geometries, in which the correct geometry in the wheel-rail contact mechanics is assured by modeling the rails as Timoshenko curved beam elements. This approach improves both the geometric representation of the rails and the accuracy of the wheel-rail contact forces calculation. A realistic operation scenario in which a multibody model of a railway vehicle runs on a flexible track with a curved geometry is used here to demonstrate the novel aspects of this work and then discuss the improvements over the conventional approaches. The results show that the proposed methodology greatly improves the computation of the wheel-rail interaction forces and prevents spurious oscillations from propagating to the vehicle.